82.0k views
1 vote
For the polynomial below, -1 is a zero,h(x)= x^3 + x^2 - 9x -9Express h (x) as a product of linear factors.

For the polynomial below, -1 is a zero,h(x)= x^3 + x^2 - 9x -9Express h (x) as a product-example-1
User Gonen I
by
4.8k points

1 Answer

1 vote

So given that -1 is a zero, we can say that a factor of the polynomial is x+1.

Then,


\begin{gathered} h(x)=x^3+x^2-9x-9 \\ h(x)=x^2(x+1)-9(x+1) \\ h(x)=(x+1)(x^2-9) \\ h(x)=(x+1)(x+3)(x-3) \end{gathered}

Therefore,

h(x) = (x+1)(x+3)(x-3)

User Jonathan Lin
by
5.2k points